Clinical performance of LOCI™-based tumor marker assays for tumor markers CA 15-3, CA 125, CEA, CA 19-9 and AFP in gynecological cancers - Ramona C Dolscheid-Pommerich; Mignon Keyver-Paik; Thomas Hecking; Walther Kuhn; Gunther Hartmann; Birgit Stoffel-Wagner; Stefan Holdenrieder (Tumor Biology)
Evidence is sparse regarding the clinical performance of luminescent oxygen channeling immunoassays–based tumor marker assays in gynecological cancer. Analyzing serum samples of 336 patients with Dimension™Vista1500, we investigated the diagnostic power of carbohydrate antigen 15-3, carbohydrate antigen 125, carcinoembryonic antigen, carbohydrate antigen 19-9, and alpha-fetoprotein in patients suffering from different types of gynecological cancer and precancerous gynecological diseases and compared findings to appropriate control groups. The cohort comprised 177 female patients with gynecological cancers (73 breast, 22 cervical, 16 endometrial, 17 vulva, and 49 ovarian cancers), 26 patients with precancerous gynecological diseases (11 vulva, 4 cervical, and 10 breast), 109 patients with benign gynecological diseases, and 24 healthy controls. Discriminative power was assessed by areas under the curve in receiver operating characteristic curves, and sensitivities were determined at a fixed specificity of 95%. Levels of biomarkers in healthy controls were in the expected ranges and a discriminative power between gynecological cancers and healthy controls was observed for several tumor markers. Established tumor type–associated markers were elevated in specific gynecological cancers and benign controls as well as within precancerous gynecological diseases and healthy control group. In ovarian cancer, carbohydrate antigen 125 and carbohydrate antigen 15-3 were significantly elevated compared to the respective benign diseases. Carbohydrate antigen 125 was the most conclusive marker (area under the curve = 0.86% and 77.6% sensitivity at 95% specificity). In breast cancer, carcinoembryonic antigen and carbohydrate antigen 15-3 were significantly higher than in the respective benign diseases. Carcinoembryonic antigen achieved the most conclusive area under the curve (0.65) with 31.5% sensitivity at 95% specificity. None of the investigated markers was found to be of value in discriminating benign and malignant cervical diseases. Carcinoembryonic antigen and alpha-fetoprotein distinguished precancerous breast and vulva diseases from healthy controls. These findings show that luminescent oxygen channeling immunoassays–based tumor marker assays provide reliable results in routine diagnostics.